Surface Functionalization by High‐precision Laser Cladding. Issue 1 (14th January 2013) - Brückner, Frank; Nowotny, Steffen; Riede, Mirko; Kubisch, Frank; Leyens, Christoph; Beyer, Eckhard
Abstract Meanwhile the laser build‐up welding technology is a well industrially established technique for highly precise coating tasks and additive manufacturing. By means of new precise powder nozzle systems, modified process equipment as well as suited manufacturing strategies, the generation of customized components can be realized up to a detail resolution within the double‐digit micrometer range. This opens a variety of new applications, e. g. in aviation, tooling industry or medical technology.